Turbulent Energy Transfer at Dipolarization Fronts - C. M. Liu; J. B. Cao; X. N. Xing; Z. Z. Chen (Geophysical Research Letters, 2023)
Abstract Dipolarization fronts (DFs), ion‐scale magnetic transients characterized by dramatic enhancement of northward magnetic field, have been documented as crucial energy transfer regions in the magnetosphere. DF‐driven energy transfer has hitherto been studied mainly in the laminar regime. Energy transfer driven by turbulent processes, however, remains unclear. Here we perform a comprehensive investigation of turbulent energy transfer (TET) developed at DFs, via using high‐cadence data from Magnetospheric Multiscale mission. We find that: (a) TET is equally governed by energy loads and generators, different from laminar energy transfer which is typically dominated by energy loads; (b) ion and electron currents play comparable roles in driving TET; (c) TET is positively correlated with local magnetic field strength and ion speed; (d) TET shows asymmetric global distributions along the dawn‐dusk direction. These features implicate that TET is primarily related to electromagnetic turbulence at electron‐ion hybrid scales. These new results, uncovering unique characteristics of DF‐driven TET, can deeply advance our understanding of energy budgets in the magnetosphere.